Adolescenti: segni e ferite. I confini della normalità - Miriam Scarciglia; Valentino Righetti (Il sogno della farfalla, 2010)
In this work the authors analyze the adolescent phase of human psycho-physical development drawing attention to the centrality of the relationship with the body and observing how for the adolescent it constitutes the subject and place of relating and of an exchange between one’s interior world and the external world, the instrument which speaks of oneself, with which to represent one’s emotions and fantasies. The analysis therefore focuses on the manipulations of the body as seen through the different forms of tattooing, piercing, diets and fashion in order to observe how during physiological development these are instruments to elaborate and narrate our experiences, they are languages without words, whereas in the presence of pathological growth, petrified by crises characterized by lack of affections, these operations on the body become exasperated and violent, self-destructive actions.